2021
DOI: 10.1055/a-1331-6939
|View full text |Cite
|
Sign up to set email alerts
|

Medical Therapy of Aggressive Pituitary Tumors

Abstract: The rare aggressive pituitary adenoma presents a special challenge, due to the heterogenous presentation of the disease. The prognosis of aggressive pituitary adenomas has been improved due to recent studies demonstrating clinically-relevant efficacy of temozolomide, which is now considered first-line chemotherapy. However, there is limited data on second-line therapies in patients with treatment failure. This review presents a summary on the potential of medical therapies in aggressive pituitary tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Clinical practice guidelines for aggressive PitNETs recommend surgery and radiotherapy for most patients, along with standard medical treatment for functioning tumours, but they become less precise when it comes to propose subsequent treatments for tumours that progress afterwards, since scientific evidence is lacking ( 1 , 18 , 19 ). We found a great variability in the treatments our patients had received prior to TMZ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical practice guidelines for aggressive PitNETs recommend surgery and radiotherapy for most patients, along with standard medical treatment for functioning tumours, but they become less precise when it comes to propose subsequent treatments for tumours that progress afterwards, since scientific evidence is lacking ( 1 , 18 , 19 ). We found a great variability in the treatments our patients had received prior to TMZ.…”
Section: Discussionmentioning
confidence: 99%
“…Corticotroph tumours, both silent and functioning, represented the most frequent lineage among these aggressive PitNETs and pituitary carcinomas, followed by lactotroph tumours, both in our cohort and all the previous multicentric studies, but we found a lower percentage of carcinomas, only 14.3%, in comparison to previously reported percentages between 19 and 32%. Clinical practice guidelines for aggressive PitNETs recommend surgery and radiotherapy for most patients, along with standard medical treatment for functioning tumours, but they become less precise when it comes to propose subsequent treatments for tumours that progress afterwards, since scientific evidence is lacking (1,18,19). We found a great variability in the treatments our patients had received prior to TMZ.…”
Section: Functioning Tumours 10mentioning
confidence: 92%
“…Tumor monitoring in rats was conducted using MRI at day 0 (pretreatment) and every 14 days post-treatment (days 14,28,42,56). MRI was performed on a 7T preclinical scanner (Bruker BioSpin MRI GmbH, Ettlingen, Germany) using previously published procedures suitable to visualize the rat pituitary tumors.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…SSAs such as Octreotide ( Figure 1 A) and Lanreotide ( Figure 1 D), which bind to somatostatin receptor 2 (SSTR2), and to a lesser extent, to SSTR5 and SSTR3, are effective in the treatment of secreting pituitary adenomas [ 11 , 12 , 13 ], but are poorly efficacious in NFPAs [ 14 ]. Similarly, the panagonist Pasireotide ( Figure 1 B), which binds to SSTR1, 2, 3, 5, showed only modest efficacy in a recent phase II clinical trial (NCT01283542—Evaluate the Efficacy and Safety of Pasireotide LAR (Long Acting Release) on the Treatment of Patients With Clinically Nonfunctioning Pituitary Adenoma—Passion I), with only 16.7% of patients reaching a tumor size reduction of at least 20% [ 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It starts with a review on the clinical implications of the new WHO classification of pituitary tumors [12], followed by manuscripts addressing the rhinological consequences of pituitary surgery [13] and the outcome of transsphenoidal surgery in prolactinomas [14], and a review article covering recent advances in craniopharyngioma [15]. An original study reports 3 cases of aggressive pituitary tumors treated by bevacizumab [16] and a more general review addresses medical options in these tumors [17]. Cushing's disease is covered by an original study reporting neuropsychologic changes in affected patients, and by reviews on mortality in Cushing's disease [18] and secondary treatment options if pituitary surgery failed [19].…”
Section: Which Topics Will You Find In This Special Issue?mentioning
confidence: 99%